Metabolic profiling of preovulatory follicular fluid in jennies. (31st December 2022) - Catalán, Jaime; Martínez-Rodero, Iris; Yánez-Ortiz, Iván; Mateo-Otero, Yentel; Bragulat, Ana Flores; Nolis, Pau; Carluccio, Augusto; Yeste, Marc; Miró, Jordi
Abstract: Follicular fluid is formed from the transudation of theca and granulosa cells in the growing follicular antrum. Its main function is to provide an optimal intrafollicular microenvironment to modulate oocyte maturation. The aim of this study was to determine the metabolomic profile of preovulatory follicular fluid (PFF) in jennies. For this purpose, PFF was collected from 10 follicles of five jennies in heat. Then, PFF samples were analysed by nuclear magnetic resonance (NMR) and heteronuclear single quantum correlation (2D 1 H/ 13 C HSQC). Our study revealed the presence of at least 27 metabolites in the PFF of jennies (including common amino acids, carboxylic acids, amino acid derivatives, alcohols, saccharides, fatty acids, and lactams): 3-hydroxybutyrate, acetate, alanine, betaine, citrate, creatine, creatine phosphate, creatinine, ethanol, formate, glucose, glutamine, glycerol, glycine, hippurate, isoleucine, lactate, leucine, lysine, methanol, phenylalanine, proline, pyruvate, threonine, tyrosine, valine, and τ-methylhistidine. The metabolites found here have an important role in the oocyte development and maturation, since the PFF surrounds the follicle and provides it with the needed nutrients. Our results indicate a unique metabolic profile of the jennies PFF, as it differs from those previously observed in the PFF of the mare, a phylogenetically close species that is taken as a reference for establishing reproductive biotechnology techniques in donkeys. The metabolites found here also differ from those described in the TCM-199 medium enriched with fetal bovine serum (FBS), which is the most used medium for in vitro oocyte maturation in equids. These differences would suggest that the established conditions for in vitro maturation used so far may not be suitable for donkeys. By providing the metabolic composition of jenny PFF, this study could help understand the physiology of oocyte maturation as a first step to establish in vitro reproductive techniques in this species. Highlights: Twenty-seven metabolites were identified in the preovulatory follicular fluid (PFF) of jennies by nuclear magnetic resonance (NMR) and heteronuclear single quantum correlation (2D 1 H/ 13 C HSQC). Jennies have their own and unique metabolic profile. This profile is different from that found in the mare, the closest phylogenetic species. Knowing the metabolic composition of the PFF of jennies could help to understand the physiology of oocyte maturation as a first step to establish in vitro reproduction techniques in the donkey.